The tumour suppressor protein LIMD1 is a novel regulator of HIF1 and the hypoxic response - Webb, Thomas M (2010)
There are three prolyl hydroxylases (PHD1, 2 and 3) that regulate the hypoxia-inducible factors (HIFs), the master transcriptional regulators that respond to changes in intracellular O2 tension. In high O2 tension (normoxia) the PHDs hydroxylate HIFα subunits on 2 conserved proline residues inducing binding of the von-Hippel-Lindau (VHL) tumour suppressor, the recognition component of a multi-protein ubiquitin-ligase complex, initiating HIFα ubiquitylation and degradation by the 26S proteasome. However, it is not known whether PHDs and VHL act separately to exert their enzymatic activities on HIFα or as a multi-protein complex. In this thesis, data are presented that shows that the tumour suppressor protein LIMD1 acts as a molecular scaffold simultaneously binding the PHDs and pVHL into a normoxic protein complex (normoxiplex), increasing their physical proximity in order to enable efficient and rapid sequential modifications and thus degradation of HIF1α. Data are presented which indicates that increased LIMD1 expression down regulates HIF transcriptional activity, by promoting HIF1α degradation via the oxygen dependent degradation domain in a manner dependent on hydroxylase and 26S proteasome activities. However, degradation of this domain is not wholly dependent on the well characterised proline residues subject to hydroxylation, suggesting that LIMD1 may alter proline hydroxylation specificity or modulate HIF via a different mechanism. Furthermore, endogenous depletion of LIMD1 results in the converse, leading to HIF1α stabilisation and accumulation, enhancing HIF transcriptional activity. Moreover, Limd1-/- MEFs show increased HIF transcriptional activity. One mechanism by which this is achieved involves the binding of PHD2 within the N-terminal portion of LIMD1 while allowing concurrent binding of VHL to the C-terminal zinc-finger LIM domains. However, the LIMD1 mediated mechanism regulating HIF1α independently of proline residues 402 and 564 is still unclear. Finally, data are presented that show that the LIMD1 family member proteins Ajuba and WTIP all bind specifically to VHL but differentially to PHDs 1, 2 and 3 and thus these three LIM domain containing proteins represent a new group of hypoxic regulators.